Radiation efficiency of a depleted cobalt-60 source for products that require low radiation doses. (September 2018) - Ounalli, L.; Mejri, A.; Mejri, N.
Abstract: To determine the radiation processing efficiency of a cobalt-60 source at the end of its useful life for products that require low radiation doses, the irradiation doses absorbed by the products were determined using the Fricke dosimeters and UV–visible spectrophotometer. Garlic " Allium sativum L. " was considered in this study because of its virtue in treating different diseases such as cancer and cardiovascular diseases and high cholesterol-lowering effect and the short time required for its irradiation. Therefore, boxes containing garlic were irradiated at 50, 100, and 150 Gy for 7, 18, and 29 min, respectively. The relative absorbed dose mapping showed a symmetrical distribution in the front and back sides of the garlic box. Thus, the cobalt-60 source was revealed to be efficient in the irradiation of garlic even at the end of its useful life. Highlights: The good irradiation practice of a cobalt-60 source at the end of its useful life was confirmed using the Fricke dosimeters. The efficiency of a cobalt-60 source at the end of its useful life in processing products that require low radiation doses was demonstrated. The dose uniformity ratio for garlic and rockwool phantom was deduced.